Traveling Black : a story of race and resistance - Bay, Mia (The Belknap Press of Harvard University Press, 2021)
"What was it like to travel while Black under Jim Crow? Mia Bay brings this dramatic history to life. With gripping stories and a close eye on the rail, bus, and airline operators who implemented segregation, she shows why access to unrestricted mobility has been central to the Black freedom struggle since Reconstruction and remains so today"--